Strategies for Short-Term Storage of Hepatocytes for Repeated Clinical Infusions. Issue 8 (August 2014) - Jorns, Carl; Gramignoli, Roberto; Saliem, Mohammed; Zemack, Helen; Mörk, Lisa-Mari; Isaksson, Bengt; Nowak, Greg; Ericzon, Bo-Göran; Strom, Stephen; Ellis, Ewa
Hepatocyte transplantation is an upcoming treatment for patients with metabolic liver diseases. Repeated cell infusions over 1–2 days improve clinical outcome. Isolated hepatocytes are usually cold stored in preservation solutions between repeated infusions. However, during cold storage isolated hepatocytes undergo cell death. We investigated if tissue preservation and repeated isolations are better than storage of isolated hepatocytes when cold preserving human hepatocytes. Liver tissue obtained from liver surgery or organ donors was divided into two pieces. Hepatocytes were isolated by collagenase digestion. Hepatocytes were analyzed directly after isolation (fresh) or after storage for 48 h at 4°C in University of Wisconsin solution (UW cells). Liver tissue from the same donor was stored at 4°C in UW and hepatocytes were isolated after 48 h (UW tissue cells). Hepatocyte viability and function was evaluated by trypan blue exclusion, plating efficiency, ammonia metabolism, CYP 1A1/2, 2C9, 3A7, and 3A4 activities, phase II conjugation, and apoptosis evaluation by TUNEL assay and caspase-3/7 activities. Hepatocytes stored in UW showed a significantly lower viability compared to fresh cells or hepatocytes isolated from tissue stored for 48 h (54% vs. 71% vs. 79%). Plating efficiency was significantly decreased for cells stored in UW (40%) compared to fresh and UW tissue cells (63% vs. 55%). No significant differences between UW cells and UW tissue cells could be shown for CYP activities or ammonia metabolism. Hepatocytes stored in UW showed a strong increase in TUNEL-positive cells, whereas TUNEL staining in cold-stored liver tissue and hepatocytes isolated after 48 h was unchanged. This observation was confirmed by increased caspase-3/7 activities in UW cells. Although preservation of isolated hepatocytes in UW maintains function, cold storage of liver tissue and repeated hepatocyte isolations is superior to cold storage of isolated hepatocytes in preserving hepatocyte viability and function.